Application of intravoxel incoherent motion perfusion imaging to shoulder muscles after a lift‐off test of varying duration. (January 2016) - Nguyen, Audrey; Ledoux, Jean‐Baptiste; Omoumi, Patrick; Becce, Fabio; Forget, Joachim; Federau, Christian
Abstract : Intravoxel incoherent motion (IVIM) MRI is a method to extract microvascular blood flow information out of diffusion‐weighted images acquired at multiple b‐values. We hypothesized that IVIM can identify the muscles selectively involved in a specific task, by measuring changes in activity‐induced local muscular perfusion after exercise. We tested this hypothesis using a widely used clinical maneuver, the lift‐off test, which is known to assess specifically the subscapularis muscle functional integrity. Twelve shoulders from six healthy male volunteers were imaged at 3 T, at rest, as well as after a lift‐off test hold against resistance for 30 s, 1 and 2 min respectively, in three independent sessions. IVIM parameters, consisting of perfusion fraction (f), diffusion coefficient (D), pseudo‐diffusion coefficient D* and blood flow‐related fD*, were estimated within outlined muscles of the rotator cuff and the deltoid bundles. The mean values at rest and after the lift‐off tests were compared in each muscle using a one‐way ANOVA. A statistically significant increase in fD* was measured in the subscapularis, after a lift‐off test of any duration, as well as in D. A fD* increase was the most marked (30 s, +103%; 1 min, +130%; 2 min, +156%) and was gradual with the duration of the test (in 10 ‐3 mm 2 /s: rest, 1.41 ± 0.50; 30 s, 2.86 ± 1.17; 1 min, 3.23 ± 1.22; 2 min, 3.60 ± 1.21). A significant increase in fD* and D was also visible in the posterior bundle of the deltoid. No significant change was consistently visible in the other investigated muscles of the rotator cuff and the other bundles of the deltoid. In conclusion, IVIM fD* allows the demonstration of a task‐related microvascular perfusion increase after a specific task and suggests a direct relationship between microvascular perfusion and the duration of the effort. It is a promising method to investigate non‐invasively skeletal muscle physiology and clinical perfusion‐related muscular disorders. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Intravoxel incoherent motion (IVIM) offers the possibility to study quantitatively microvascular perfusion properties of skeletal‐striated muscle. We applied this method to the shoulder muscles after a lift‐off test of various duration, which is a test used in daily clinical practice to specifically assess the integrity and functionality of the subscapularis muscle. We found a selective increase in IVIM perfusion parameters in the subscapularis and posterior deltoid muscles.